SIFAT-SIFAT PAPAN PARTIKEL KAYU KELAPA - Rozak Memed; Paribotro Sutigno; I M Sulastiningsih (Pusat Penelitian dan Pengembangan Hasil Hutan, 1984)
This report deals with the laboratory tests on the properties of particle board made from coconut wood and from coconut wood with hardwood bonded by urea formaldehyde. The tests include board density, moisture content, water absorption, thickness swelling and bending strength.The result reveals that physical and mechanical properties of particle boards made from coconut wood conform with FAO Standard. The properties of particle boards made from coconut wood mixture with hardwood in the proportion of 1 : 1 which conform the FAO Standard are limited to density and water absorption.